The Analysis of Quality of Technology of Local Oxidation - Anilionis, R.; Keršys, T. (Elektronika ir Elektrotechnika, 2004)
Problems of technology LOCOS, related with local oxidation of a epitaxical layer was researched. A lot of problems arise because of an irregularity of an oxidized surface. Using program SUPREM, mathematical modeling of local growth of silicon is carried out. Designed profiles of oxide LOCOS, depending from hole in a epitaxical layer, and also from operating conditions of oxidation: temperature and time. It is determined, that most acceptable results are received when the form of hole is similar to a trapezoid, and oxidation descends in wet oxygen, at 1100 ºС. Ill. 9, bibl. 3 (in Lithuanian, summaries in Lithuanian, English and Russian).